2019
DOI: 10.9734/jpri/2019/v31i630319
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Topical Clobetasol among the Women in Hail Region, Saudi Arabia: A Cross-sectional Study on Knowledge and Practice

Abstract: Aims: The current study aimed to evaluate female consumers’ knowledge and practice about harmful effects of topical clobetasol applied on the face for cosmetic purposes.  Study Design: Cross-sectional study.  Place and Duration of Study: Randomly selected community pharmacies, well known cosmetic shops and shopping malls of Hail region, Saudi Arabia from March 2018 to June 2018. Methodology: We included 391 participants who only used ‘clobetasol’ as a topical steroid at the time of interview,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…This matched the results of another study: 44% of women who used the topical steroids received the prescription from a doctor [ 10 ]. Among those who used unprescribed topical steroids, family and friends were the main sources of advice, similar to the other local study, which revealed that the leading inspirations toward the usage of facial TCs were relatives and friends [ 3 , 5 ].…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…This matched the results of another study: 44% of women who used the topical steroids received the prescription from a doctor [ 10 ]. Among those who used unprescribed topical steroids, family and friends were the main sources of advice, similar to the other local study, which revealed that the leading inspirations toward the usage of facial TCs were relatives and friends [ 3 , 5 ].…”
Section: Discussionsupporting
confidence: 77%
“…In 1951, topical corticosteroids (TCs) were used for the first time by American dermatologist Marion Baldur Sulzberger [ 2 ]. In modern dermatological practice, TCs have become one of the most widely used treatment methods [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations